Tinzaparin for the Management of Cancer Associated Thrombosis in Patients with Cancer: a Budget Impact Analysis from the Italian Healthcare System Perspective - Lorenzo Giovanni Mantovani; Ippazio Cosimo Antonazzo; Paolo Angelo Cortesi (Farmeconomia: Health Economics and Therapeutic Pathways)
BACKGROUND: Venous thromboembolism (VTE), which includes deep vein thrombosis (DVT) and pulmonary embolism (PE), is a significant health problem with especially increased prevalence, morbidity and mortality in patients with cancer. This study aimed at assessing the economic impact of tinzaparin in patients with cancer associated thrombosis (CAT).